Evaluation of the prognostic factors for candidemia in a medical intensive care unit - Kır, Seher; Bahceci, Buğra Kaan (Journal of Surgery and Medicine, 2020)
Aim: Infections with Candida species are an important cause of morbidity and mortality in intensive care units (ICUs). The studies about the prognostic factors related with candidemia in ICU patients are limited and lacking in our country. The aim of this study is to evaluate the epidemiology and prognostic factors for candidemia in adult patients admitted to a medical ICU. Methods: This is a retrospective cohort study. A total of 693 patients who were followed for more than 48 hours in our 16-bedded medical ICU between 2016 October-2019 March were evaluated retrospectively and 60 candidemia patients were included in the study. The patients were divided into two groups according to ICU mortality (survivor vs. non-survivor) and compared to determine possible prognostic factors among Candida infection risk factors. Results: The total incidence of candidemia was 46 per 1000 admissions. The most common fungal isolate was Candida albicans (57.5%). The 30-day mortality was 71.7% and ICU-mortality was 78.3%. There was no difference for age, gender, co-morbid diseases, SOFA and APACHE II scores, Glasgow Coma Score, immunosuppressive treatments (steroid or chemotherapy), septic shock, neutropenia, acute hepatic or renal failure, need for vasopressors, hemodialysis, erythrocyte transfusion and total parenteral nutrition between groups. No relationship was found between the time of initiation of antifungal therapy and mortality (P=0.268). Survivors had shorter ICU stay and hospital stay before ICU, and lower Charlson Comorbidity Index scores than non-survivors (P=0.039, P=0.008, P=0.02, respectively). Length of hospital stay before ICU, need for invasive mechanical ventilation and hypoalbuminemia were the prognostic factors for ICU mortality of candidemia patients (P=0.034, P=0.013, P=0.029, respectively). Conclusion: We reported the highest incidence rate of candidemia and one of the highest mortality rates in critically ill patients with candidemia. Confirming to most of the previous reports, Candida albicans (57.5%) was the most common isolate in our study. We evaluated reported risk factors for invasive candidiasis as a prognostic indicator for candidemia in ICU patients, and found that the length of hospital stay, invasive mechanical ventilation and hypoalbuminemia were prognostic indicators.